NPH Presenting As Parkinsonism And Early Optic Atrophy - Khan, N A; Bashar, M A; Huq, N A; Salma, U (Journal of Dhaka National Medical College & Hospital, 2015)
An old hypertensive patient presented with progressive slowness of movement and difficulty in walking for 6 months. He also complained of the gradual memory loss with blurring of vision (left eye more than right) and incontinence of urine. Patient was confused with slow, indistinct speech and lead-pipe and cogwheel rigidity in both upper and lower limbs. Mild weakness in left side of body with left plantar extensor. Primitive reflexes were present. CT scan of brain showed multiple lacunar infarcts with grossly dilated 3rd, 4th and lateral ventricle with rounding of frontal horns and minimal dilatation of sulci. Finally he was diagnosed as parkinsonism secondary to NPH (Normal pressure hydrocephalus). Although extrapyramidal feature in NPH are not uncommon, presentation with parkinson syndrome as a predominant feature is rare. Failure of the patient with parkinsonism to respond to levodopa therapy, should alert one about the possibility of NPH J. Dhaka National Med. Coll. Hos. 2015; 21 (01): 52-54